Effectiveness of Basil Leaf Extract (Ocimum Sanctum Linn) on Aedes Aegypti Larva Death - Desi Eka Putri; Nurfadilah; Yuli Hayati; Fitriannindyah Yudha Ariesta; Herni Misriani (PT FORMOSA CENDEKIA GLOBAL, 2024)
Dengue Hemorrhagic Fever is a disease caused by the Dengue virus which is transmitted to humans through the bite of the Aedes Aegypti and Aedes Albocpictus mosquitoes. Aedes Aegypti is a species of tropical and sutropic mosquito found on earth. Aedes Aegypti is one of the most efficient mosquito vectors for arboviruses, because this mosquito is very anthropophilic and lives near humans and often lives indoors. Basil (Ocimum sanctum Linn) is a plant that is widely known by the Indonesian people. Basil contains flavonoid compounds and saponins. Flavonoids and saponins can be used as insecticides and larvicides. The aim of this research is to determine the effectiveness of basil leaf extract on the death of Aedes Aegypti larvae in RT 03 RW 03, Citamiang District, Citamiang Village, Sukabumi City in 2018. This type of research is an experiment with doses of 10ml, 15ml, 20ml and 25ml with 4 repetitions. The population used was 250 Aedes Aegypti larvae, each filled with 10 individuals in each container and taken from RT 03 RW 03, Citamiang District, Citamiang Village, Sukabumi City in 2018. The data analysis used was Univariate Analysis and Bivariate Analysis using SPSS. From the results of the Univariate Analysis research, the most effective death of Aedes aegypti larvae at a dose of 25 ml was 36 larvae. And the results of the Bivariate Analysis calculations obtained a P-Value value of 0.000 < 0.05, thus showing that there was an influence of Basil Leaf Extract (Ocimum Sanctum Linn) on the death of Aedes aegypti larvae RT 03 RW 03 Citamiang District, Citamiang Village, Sukabumi City in 2018. It is recommended for future researchers to use a larger number of larvae so that the data obtained is more representative. Apart from that, it is hoped that the public can use Basil Leaf Extract as a vegetable insecticide in mosquito breeding areas.